Hubungan Kadar Interleukin 6 (IL-6) dengan Derajat Aktivitas Penyakit (SLEDAI-2K) dan Manifestasi Kerusakan Renal-Non-Renal Penderita Lupus Eritematosus Sistemik: Penelitian - Sianturi, Yesanopa; Rangkuti, Deske Muhadi; Ginting, Andi Raga (Cermin Dunia Kedokteran, 2026)
Introduction: Systemic lupus erythematosus (SLE) is a chronic, heterogeneous, and complex autoimmune disease. Several studies have linked IL-6 levels and SLE. This study sought to investigate the relationship between IL-6 levels and degree of disease activity and manifestations of renal-non-renal damage in SLE. Methods: A retrospective cross-sectional study of 67 SLE patients based on the SLICC 2012/ACR EULAR 2019 criteria for at least 6 months at the Rheumatology Polyclinic of AM General Hospital, Medan from June to August 2023 who met the inclusion and exclusion criteria. Assessment of renal-non-renal damage used the SLICC DamageIndex-SDI score and the degree of disease activity was measured with SLEDAI-2K. Results: The highest median IL-6 level of 87.32 pg/mL was found in the remission group, while the lowest median IL-6 level of 46.05 pg/mL was found in patients with mild disease. No significant relationship between IL-6 levels and the degree of SLE disease activity (p = 0.158). The median interleukin-6 value in the group of subjects with renal damage was 71.95 pg/mL, while in the group of subjects with non-renal damage it was 53.05 pg/mL. No correlation was found between IL-6 levels and disease activity (p = 0.158), but there was a significant correlation between IL-6 levelsand renal damage (p = 0.045). Conclusion: No relationship between IL-6 levels and the degree of disease activity (p = 0.158), but a significant relationship between IL-6 levels and renal damage (p = 0.045).